Anticipation de l’emploi de la préposition verbale « à » et les interférences français-espagnol - Rouanne, Laurence (Thélème. Revista Complutense de Estudios Franceses, 2010)
The differences in the verbal construction between French and Spanish, as well as the differences, within traditional classifications, regarding the notions of transitivity and in transitivity, direct and indirect objects , are the origin of significant interferences. We propose a description of the French verb system based on the type of objects taken and provide a comprehensive list of the transitive verbs which take only one object. The aim of this work is to illustrate that it is possible to provide students with a reliable resource which can help them predict the rule for any verb.
Keywords: Verbal construction; Verb rules; Preposition; Object